Mechanisms of Chronic State of Inflammation as Mediators That Link Obese Adipose Tissue and Metabolic Syndrome - Eduardo Fuentes; Francisco Fuentes; Gemma Vilahur; Lina Badimon; Iván Palomo (Hindawi Limited, 2013)
The metabolic syndrome is a cluster of cardiometabolic alterations that include the presence of arterial hypertension, insulin resistance, dyslipidemia, and abdominal obesity. Obesity is associated with a chronic inflammatory response, characterized by abnormal adipokine production, and the activation of proinflammatory signalling pathways resulting in the induction of several biological markers of inflammation. Macrophage and lymphocyte infiltration in adipose tissue may contribute to the pathogenesis of obesity-mediated metabolic disorders. Adiponectin can either act directly on macrophages to shift polarization and/or prime human monocytes into alternative M2-macrophages with anti-inflammatory properties. Meanwhile, the chronic inflammation in adipose tissue is regulated by a series of transcription factors, mainly PPARs and C/EBPs, that in conjunction regulate the expression of hundreds of proteins that participate in the metabolism and storage of lipids and, as such, the secretion by adipocytes. Therefore, the management of the metabolic syndrome requires the development of new therapeutic strategies aimed to alter the main genetic pathways involved in the regulation of adipose tissue metabolism.